Efeitos de futuros regimes de precipitação no escoamento superficial e produção de sedimentos em uma bacia da região semiárida do Brasil - Frade, Tatiane Gomes (2023)
Water availability and sediment production in semi-arid basins are influenced by climate change, among others, which poses a threat to the ecosystem and the management of water resources. It is noticed that hydrological droughts have gradually increased in severity, duration and occurrence over the years, which raises the attention of researchers about future impacts on water availability and sediment production caused by climate change. This study aimes of estimating the production of sediments occurred in future hydrological drought events in the Piancó River basin, based on future climate scenarios based on the emission of greenhouse gases. The effects of future precipitation regimes on surface runoff and sediment production in a basin in the Brazilian semi-arid region were analyzed based on the Soil and Water Assessment Tool (SWAT) model and the Streamflow Drought Index (SDI). In this study, two future climate scenarios were analyzed, RCP 4.5 (optimistic) and RCP 8.5 (pessimistic). For the calibration of the SWAT model, the software SWAT Calibration and Uncertainty Programs (SWAT-CUP) was used, with the calibration period from 1993−2005 and the validation period from 2008−2012. After these procedures, the climate forecast data of the scenarios optimistic and pessimistic were used to obtain future time series of flow and sediment production, using the SWAT model. Then, the SDI was calculated based on the series of simulated future flows for the identification of drought events in the basin. The results of the study showed that the calibration and validation of the model presented very good adjustments: R² = 0.83 and NSE = 0.82 and R² = 0.89 and NSE = 0.77, respectively. There were reductions in flow volume of -75.86% and sediment production of -86.5%, when comparing the scenarios, with a significant reduction in the contribution of sediments to the outlet. It was noticed that, according to the SDI, the most critical years related to drought events did not coincide in the different scenarios addressed (pessimistic and optimistic). In addition, the occurrence of long periods of drought was also verified in all the time scales used. The transition matrix demonstrated the high probability of occurrence of drought events occurring in successive years, in addition to demonstrating the propagation of droughts in different time scales (3, 6, 9 and 12 months) in each hydrological year. Spatially, a concentration of sediment production was noticed in the portion referring to the source of the BHRP. Finally, the close relationship between the occurrences of hydrological drought and the variation in the quantity of sediment production in future scenarios in the BHRP was perceived.